Debate: Supporting the mental health of school students in the COVID‐19 pandemic in New Zealand – a digital ecosystem approach. Issue 4 (7th October 2020) - Merry, Sally N.; Cargo, Tania; Christie, Grant; Donkin, Liesje; Hetrick, Sarah; Fleming, Terry; Holt‐Quick, Chester; Hopkins, Sarah; Stasiak, Karolina; Warren, Jim
Abstract : The pandemic is creating unprecedented demand for mental health support for young people. While schools often facilitate mental health support for their students, the demands for online teaching and the uncertainty created by the pandemic make traditional delivery of support through schools challenging. Technology provides a potential way forward. We have developed a digital ecosystem, HABITS, that can be integrated into school and healthcare systems. This has allowed us to deploy specific evidence‐based interventions directly, and through schools, to students and to parents in New Zealand during the current pandemic. Chatbot architecture is particularly suited to rapid iteration to provide specific information while apps can provide more generalised support. While technology can provide some solutions, it is important to be aware of the potential to increase current inequities, with those facing the greatest challenges to health and well‐being, also least able to afford the resources to access digital interventions. Development of an integrated and equitable digital system will take time and collaboration.